DEVELOPMENT OF ETHNOSCIENCE PUZZLE GAME FOR CHILDREN WITH SPECIAL NEEDS - Wahyuni Fajar Arum; Erwan Eko Prasetyo (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2019)
Science is the science that underlies the development of technology that is used to obtain an explanation relating to objects and phenomena that occur in everyday life. The purpose of this study is to develop science by using learning media in the form of puzzles with Javanese local wisdom to determine the learning activities and motivation of children with special needs. The research method used is a mixed method in which research uses qualitative and quantitative methods. While the data collection techniques used were interviews, documentation, and observation to determine the learning activities and motivation of children with special needs. The sampling technique used in this study was purposive sampling area with a total sampling of seven children with special needs in the Panti 2 Yayasan Sayap Ibu Sampling was carried out for children in the Panti 2 Yayasan Sayap Ibu. Finally, the puzzle game can determine the activities and motivations of students with special needs. Therefore, it is important to develop learning media (game)based on local wisdom for children with special needs.